Educação indígena Ticuna e o processo de afirmação étnica na escola municipal Ebenézer - Catachunga, Eli Leão (2021)
The research investigated at the school level whether the pedagogical processes and practices attributed to Ticunas children and young people considered the culture of the people, strengthening and affirming their ethnic identity. The general objective was to understand the relevance of the traditional and mythological knowledge of the Magüta people in formal education through the historical trajectory of the Ticuna people. For this, the didactic material and documents of the Ebenezer indigenous school and the school's political pedagogical project were analyzed. Theoretical research was anchored in Elias (1990), Franz Boas (2005), Bronislaw Malinowski (1986), Evans-Prichard (1993), Clifford Geertz (2001), Arnold Vann Gennep (2013), Darcy Ribeiro (2000) Marcel Mauss (1974) and Lévi-Strauss (2003). And the methodology used was qualitative, field, oral history and life perspective, participant observation, with open, unstructured interviews. In this way, it was intended to capture the interpretation of people and their own lives and describe the importance of the value and maintenance of traditional and mythological Ticuna knowledge in contemporary education.